Synthesis and characterization of CuO nanofibers, and investigation for its suitability as blocking layer in ZnO NPs based dye sensitized solar cell and as photocatalyst in organic dye degradation - Sahay, R. (2014)
10.1016/j.jssc.2011.12.013